Bidirectional roles of the Ccr4-Not complex in regulating autophagy before and after nitrogen starvation. Issue 2 (1st February 2023) - Yin, Zhangyuan; Zhang, Zhihai; Lei, Yuchen; Klionsky, Daniel J.
ABSTRACT: Macroautophagy/autophagy is a highly conserved catabolic process by which cytoplasmic constituents are delivered to the vacuole/lysosome for degradation and recycling. To maintain cellular homeostasis and prevent pathologies, the induction and amplitude of autophagy activity are finely controlled through regulation of ATG gene expression. Here we report that the Ccr4-Not complex in Saccharomyces cerevisiae has bidirectional roles in regulating autophagy before and after nutrient deprivation. Under nutrient-rich conditions, Ccr4-Not directly targets the mRNAs of several ATG genes in the core autophagy machinery to promote their degradation through deadenylation, thus contributing to maintaining autophagy at the basal level. Upon starvation, Ccr4-Not releases its repression of these ATG genes and switches its role to promote the expression of a different subset of ATG genes, which is required for sufficient autophagy induction and activity. These results reveal that the Ccr4-Not complex is indispensable to maintain autophagy at the appropriate amplitude in both basal and stress conditions.Abbreviations : AID, auxin-inducible degron; Ape1, aminopeptidase I; Atg, autophagy related; Cvt, cytoplasm-to-vacuole targeting; DMSO, dimethyl sulfoxide; IAA, indole-3-acetic acid; PA, protein A; RIP, RNA immunoprecipitation.